STRENGTHENING POLICY RESEARCH : ROLE OF THINK TANK INITIATIVE IN SOUTH ASIA - SUKHADEO THORAT, Etal (LONDON SAGE, 2019)
An engaging presentation of policy research by various think tanks in South Asia and its facilitation by the Think Tank Initiative.
Keywords: POLICY SCIENCE; SOUTH ASIA